THE CLASSROOM MANAGEMENT PRACTICES OF YOUNG TEACHERS IN PUBLIC SECONDARY SCHOOLS IN ENUGU STATE, NIGERIA - Nnenna Amoke, Josephine; Ngozi Ezeaku, Felicia; Chukwuemeka-Nworu, Ijeoma Joyce; Amunabo Okwo, Fedrick; Enyi, Chinwe; Ndukwe Ukpai, Eke; Ngozi Nwafor, Bernadette; Chinwe Diara, Faith; Chinwe Omeke, Faith (International Journal of Psychosocial Rehabilitation, 2021)
The study examined the classroom management practices of young teachers in public secondaryschools in Enugu State, Nigeria. Two research questions and one null hypothesis guided thestudy. The population of the study was all the 329 teachers of public secondary schools in thezone who has not taught for more than 4years, in 2016/2017 academic session. The sample usedfor the study was 120 teachers randomly selected from the three local government areas in thezone. A 20- item structured questionnaire developed by the researcher was used for datacollection. The instrument was validated by two experts in Educational Administration andPlanning and one from Measurement and Evaluation, all from University of Nigeria, Nsukka.The results were analysed using mean scores and standard deviations to answer the researchquestions, while t-test was used to test the hypothesis at 0.05 level of significance. The resultsshowed that the performance of young teachers in classroom management in public secondaryschools in Enugu State was low. It was also revealed that location of schools had no significanteffect on performance of the young teachers. It was recommended among others that theMinistry of Education, Post Primary School Management Board and Administrators of schoolsshould organize workshops, conferences and formal mentoring programmes for newly recruitedteachers in the State.